Marginalities in India: Themes and Perspectives - Basu, Sudeep; Bhattacharyya, Asmita (Singapore : Imprint: Springer, 2018)
This volume engages with the renewed focus on various forms of persisting and new marginalities in globalising India. The persistence of hunger in pockets of India; forcible land acquisitions and their impact on deprived sections of society; the effects of urban relocations; material deprivation of minority groups and tribes as a result of conflicts; continuing caste discrimination; reported cases of atrocities against lower castes and tribes; regional disparities; gendered forms of exclusion and those related to disability and many other conditions suggest the need to rethink notions and practices of marginality and exclusion in India. This volume critiques the principal ways of thinking about marginalities, which primarily consist of a focus on normative principles, and brings into focus the chasm between such principles and subjective notions and experiences of marginality and injustice. The uniqueness of this edited volume is that it connects theoretical perspectives with empirical case studies and discussions, and cases of exclusion are discussed within an overall inclusive and integrated framework. This is a valuable resource for researchers, scholars, students, public policy formulators and for social innovators from private sectors and non-government organisations.
Part I Conceptual considerations -- Chapter 1. Situating Marginalities in India: An Introduction -- Chapter 2. Marginality, Marginalisation and the Idea of Justice Partha Nath Mukherji. -Part II Marginalities of yore: Caste -- Chapter 3. Rethinking Dalit Marginality Sudeep Basu -- Chapter 4. Social Exclusion and the Mindscapes of Caste: A study of Kendrapara district of Odisha Suratha Kumar Malik -- Part III Development, Displacement and the Tribal question -- Chapter 5. Displacement and Deprivation in Jharkhand Pankaj Kumar -- Chapter 6. The State and the Autochthons: Development Induced Conflict in Sikkim Binu Sundas -- Chapter 7. Revisiting Naxalbari: Narratives of Violence and Exclusions from the Marginal Spaces Arnab Roy Chowdhury -- Chapter 8. Local Communities in Forest Management: An Evaluation Anurima Mukherjee Basu -- Chapter 9. Land Laws, Ownership and Tribal Identity: The Manipur Experience Ngamjahao Kipgen -- Chapter 10. Migrant Tribes in a Globalising City: Educational Views, Aspirations and Choices of the Santals in Kolkata Ruchira Das -- Part IV Minority and Gendered Positions: An Intersectional Perspective -- Chapter 11. The Marginal Locations of Muslim Women on Various Sites in India Esita Sur -- Chapter 12. Reassessing the Socio-Economic condition among Muslim and Hindus: Comparative accounts Santanu Panda -- Chapter 13. Unmasking the Masked Gendered Sociability: A Case of the Indian Software Industry Asmita Bhattacharyya -- Chapter 14. Negotiating Marginality: Women activists in the People's Science Movement, Kerala Shoma Choudhury Lahiri -- Part V Embodied marginalities or New marginalities -- Chapter 15. Being Eunuch, the Violence faced by Hijra's involved in Sex Work - A Case Study Rekha Pande.<- Chapter 16. Transition of Elderly from Home to Old Age Home: A Narrative on Marginalisation and Seclusion in Urban India Smita Verma -- Chapter 17. Rights of Physically Disabled Persons: An Inclusive approach Sadhna Gupta -- Part VI. Political geography of violence -- Chapter 18. Statelessness or Permanent Rehabilitation: Issues Relating to the Chakmas of Chittagong Hill Tract in Arunachal Pradesh and Tripura Anindita Ghoshal -- Chapter 19. Historical Memory and the Method of Collaboration: Doomed Marginal Resistance Movements? Javaid Iqbal Bhat.
Includes index.
Description based on publisher-supplied MARC data.
Keywords: SOCIAL INEQUALITY; SOCIAL STRUCTURE; SOCIAL STRUCTURE; SOCIAL INEQUALITY